Let Tiebout pick up the tab: Pricing out externalities with free mobility - Hiroki Watanabe (European Regional Science Association (ERSA), 2016)
Free mobility has not been thought of as an effective tool to correct over- or underproduction of externalities. In this paper, we establish that foot voting can internalize the cost of negative externalities. Workers have to accept the wage and rent, however high or low they are in equilibrium, if they cannot relocate. In reality, they are mobile and they can effectively influence the equilibrium wage and rent to reflect the externalities by threatening to walk away if the current externalities are at an intolerable level. Firms indirectly pay for the damage in the form of an increased labor or land cost and thus the externalities are partially internalized in an open city as opposed to a closed city. We will specify the condition under which an open equilibrium is efficient in the presence of externalities, and discuss potential policy implications of our findings.
Keywords: D62; R23; R13; Q5; 330; Externality; Foot Voting; Quality of Life; Production Economy